2017
DOI: 10.3390/rs9010099
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of the Urban Built-Up Environment on Plant Phenology Using Fused Satellite Data

Abstract: Abstract:Understanding the effects that the Urban Heat Island (UHI) has on plant phenology is important in predicting ecological impacts of expanding cities and the impacts of the projected global warming. However, the underlying methods to monitor phenological events often limit this understanding. Generally, one can either have a small sample of in situ measurements or use satellite data to observe large areas of land surface phenology (LSP). In the latter, a tradeoff exists among platforms with some allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Data fusion is also a promising way to acquire high spatial-temporal resolution data, regardless of the weather condition. The derived multitemporal Landsat-like NDVI data used in this study have high spatial resolution and a medium temporal resolution that can be used to identify paddy rice and capture the phenology of vegetation [39,[95][96][97]. Moreover, using the fused time series can produce accurate vegetation (especially crops) distributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data fusion is also a promising way to acquire high spatial-temporal resolution data, regardless of the weather condition. The derived multitemporal Landsat-like NDVI data used in this study have high spatial resolution and a medium temporal resolution that can be used to identify paddy rice and capture the phenology of vegetation [39,[95][96][97]. Moreover, using the fused time series can produce accurate vegetation (especially crops) distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding complex heterogeneous areas, high temporal and spatial variations might lead to greater prediction errors than in homogeneous areas. Different temporal growing patterns of vegetation and spatial heterogeneity in the study area might account for this [97]. Concerning a CNN, the proposed method does not consider the spatial pattern of the study area, which is also a key factor for discriminating vegetation types.…”
Section: Discussionmentioning
confidence: 99%
“…In Shanghai, China, for example, the average rural-urban difference was approximately 5-10 days using Landsat EVI (30 m) during 2001-2010 [26] compared to 7-15 days using SPOT NDVI (1 km) during 2002-2009 [27]. Similarly, in Salt Lake City, United States, the average rural-urban difference was greater than 15 days using MODIS EVI (500 m) during 2003-2012 [24] while the average rural-urban difference was less than 3.56 days using fused NDVI (30 m) during 2000-2011 [28]. From these examples, it is noticeable that urbanization effects on vegetation spring phenology using images with coarser resolutions is larger than finer resolutions, which implies large uncertainties when using satellite images to study these effects.…”
Section: Introductionmentioning
confidence: 88%
“…Knowledge of these reason(s) can improve the accuracy and reliability of the future studies on this topic. (30 m ) TIMESAT Salt Lake City, United States Less than 3.56 [28] 1 D means average difference of vegetation spring phenology between rural and urban areas; 2 LPA means Landsat phenology algorithm; 3 Fused NDVI means NDVI time series derived from Landsat and MODIS fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Even more recently, a study fused MODIS and Landsat reflectance data in addition to LST derived from Landsat thermal data and found that in general, Ogden, UT experienced earlier start of season, later end of season, and consequently longer length of season than the surrounding exurban areas [26].…”
Section: Introductionmentioning
confidence: 99%